The chief technology officer (CTO) in theory and practice: A literature review and results from field research in Japan - Cornelius Herstatt; Frank Tietze; Akio Nagahira; David Probert (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2006)
This paper presents a literature review discussing empirical as well as conceptual papers concerning the CTO - the Chief Technology Officer - his tasks, responsibilities and authority and his relations with other corporate functions. It further presents first results of a CTO survey conducted in the Japanese electrical engineering industry in the fall of 2006. Based on both, a set of propositions is presented which the authors test via a large forthcoming empirical study in the same industry.
Keywords: 650